2013
DOI: 10.1186/1746-6148-9-103
|View full text |Cite
|
Sign up to set email alerts
|

Differentially expressed proteins in the skin mucus of Atlantic cod (Gadus morhua) upon natural infection with Vibrio anguillarum

Abstract: BackgroundVibriosis caused by V. anguillarum is a commonly encountered disease in Atlantic cod farms and several studies indicate that the initiation of infection occurs after the attachment of the pathogen to the mucosal surfaces (gut, skin and gills) of fish. Therefore it is necessary to investigate the role of different mucosal components in fish upon V. anguillarum infection. The present study has two parts; in the first part we analyzed the differential expression of skin mucus proteins from Atlantic cod … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
67
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 56 publications
2
67
0
Order By: Relevance
“…In certain agreement with our data, impa gene was up-regulated in European eel and Nile tilapia fish species stressed by seawater change [44]. At proteome level, this protein was identified in skin mucus of Atlantic cod after infection [22], suggesting a role in disease protection on fish.…”
supporting
confidence: 91%
See 2 more Smart Citations
“…In certain agreement with our data, impa gene was up-regulated in European eel and Nile tilapia fish species stressed by seawater change [44]. At proteome level, this protein was identified in skin mucus of Atlantic cod after infection [22], suggesting a role in disease protection on fish.…”
supporting
confidence: 91%
“…It was reported that GST levels increased after exposure to pyrethroids [48]. In addition, GST omega 1 was over-expressed in skin mucus of Atlantic cod after infection [22]. According with these studies, after 30 days of overcrowding stress the oxidative stress by GST over-expression in skin mucus of gilthead seabream could increase.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…Roland et al 2013;Wang et al 2013) or pathogens (e.g. Mu et al 2013;Rajan et al 2013). Indeed, Chinese researchers have applied proteomics technologies to gain a deeper understanding of pathogens and disease in aquaculture; moreover, the use of immunoproteomics was proven successful for the identification of vaccine candidates (see review by Peng 2013).…”
Section: Molecular and Biochemical Tricks Of The Aquaculture Researchmentioning
confidence: 99%
“…ApoE was found to work as an immune modulator in human (Tenger and Zhou 2003) and to possess antiviral (Dobson et al 2006;Kelly et al 2010), antibacterial (Forbes et al 2013), and antifungal (Rossignol et al 2011) activities. As an orthologous to mammalian apoA-II, apo-14 is a fish-specific fundamental constituent of high-density lipoprotein (Choudhury et al 2009), and is up-regulated in liver of European seabass (Dicentrarchus labrax) infected with Vibrio anguillarum (Sarropoulou et al 2009), in skin mucus of Atlantic cod (Gadus morhua) naturally infected with V. anguillarum (Rajan et al 2013), and in liver and gill of grass carp infected with parasitic copepod Sinergasilus major (Chang et al 2005). In a high-throughput transcriptome analysis of turbot (Scophthalmus maximus) with viral infection stimulus, apo-14 was also revealed to be the second highly expressed gene (Pereiro et al 2012).…”
Section: A+d*02mentioning
confidence: 99%